A Content Analysis of the English Textbook Entitled â€œBright an English 2â€ - Puspita Mahardika Prasetyaningtyas; Januarius Mujiyanto; Djoko Sutopo (Universitas Negeri Semarang, 2022)
Textbook plays a vital role in facilitating students’ learning. However, the content of the textbook sometimes does not meet students’ needs. From this standpoint, this study shed light on the content analysis of an English textbook used in junior high school. By focusing on the analysis of exercises in an English textbook entitled Bright an English 2, this study aimed at describing discourse competence, sociocultural competence, formulaic competence, interactional competence, linguistic competence, and strategic competence. This research applied a qualitative research design with a content analysis approach. The object of the study was Bright 2 English textbook for 8th graders of Junior High School. The research used documentation techniques for collecting the research data. Descriptive qualitative analysis was used for analyzing the data. The findings show (1) the discourse competencies found in the textbook are cohesion, coherence, deixis, and generic structure, (2) the sociocultural competencies that are existed in English skill tasks are social contextual factors, stylistic appropriateness, and cultural factors, (3) the formulaic competencies found is collocation, (4) the interactional competencies found are actional competence, conversational competence, and non-verbal communication, (5) the linguistics competencies found are syntax, morphology, lexicon, and phonology, and (6) the strategic competencies found are interacting strategy. Based on those findings, it can be concluded that the English textbook Bright an English 2 is suitable for English learners’ needs. The analysis of this textbook could help to ensure that the material presented in the textbooks is accurate and aligned with the curriculum goals and students’ needs.